Influence of shield wires on geomagnetically induced currents in power systems. (May 2020) - Liu, Chunming; Boteler, David H.; Pirjola, Risto J.
Highlights: This study investigate multiple ways in which shield wires can influence the GIC in power grids. The effect of shield wires on the effective substation grounding resistance is proved to be the only one that significant. A simple formula is given to include the effect of shield wire in GIC modelling. Abstract: There is increasing interest in assessing the GIC risk to power systems with GIC disturbing events to power systems observed in many parts of the world. An essential step in GIC risk assessment is modeling of GIC. Many factors have been considered in the GIC network model, but the effect of shield wires is still not clear. In this paper, we investigate multiple ways in which shield wires can influence the GIC in the transmission lines, including: mutual inductance between the shield wire and the transmission line, voltage change in substation grounding resistance due to GIC flowing to/from the shield wire, the geoelectric field distortion due to GIC flowing to/from the shield wire through tower footings and the influence of shield wires on the effective substation grounding resistance. Typical values for each effect are calculated to determine the significance of the shield wire effect on GIC. For the situations considered, the effect of shield wires on the effective substation grounding resistance is the only one that significantly affects GIC in transformers. To include this effect in GIC modeling a simple formula is given for the resistance of a shield wire and tower network.